Pengaruh Evaluasi Grade Serta Jari Jari Tikungan dan Superelevasi Terhadap Produktivitas Alat Angkut Overburden pada Pit Pinang PT Bukit Baiduri - Tito Arie Ananta Mahendra; Agus Winarno; Rety Winonazada; Harjuni Hasan; Tommy Trides (Jurnal Sains dan Teknologi, 2026)
PT. Bukit Baiduri Energi (BBE) is a coal mining company that utilizes hauling roads as the main infrastructure for material transportation. This study focuses on a 1.7 km road segment selected as the object of technical evaluation. The objective of this research is to analyze the effect of road geometry improvements on hauling time efficiency and equipment productivity. The method employed includes direct field measurements and calculations of operational parameters such as travel time, cycle time, and productivity. The results indicate that improvements in road grade reduced travel time from 10.13 minutes to 9.86 minutes. This reduction was followed by a decrease in cycle time from 16.29 minutes to 16.22 minutes. In addition, productivity increased from 65.4 bcm/hour to 66.69 bcm/hour. Also, improvements in curve radius and superelevation were implemented on the hauling road. These improvements resulted in a further decrease in travel time from 9.86 minutes to 8.6 minutes. Consequently, the cycle time also decreased from 16.22 minutes to 16.18 minutes. The productivity of hauling equipment increased from 66.69 bcm/hour to 67.02 bcm/hour. Overall, the evaluation of road geometry provided a positive contribution to operational performance. The productivity of overburden removal increased from 65.4 bcm/hour to 67.02 bcm/hour, representing an improvement of 2.48%.